A review of the hague visby rules in respect of the international carriage of goods by sea: existing practices and problems / Muhammad Radhi Azizan, Nur Ashikeen Khamis - Azizan, Muhammad Radhi; Khamis, Nur Ashikeen (2007)
The research paper is regarding The Hague Visby Rules giving emphasized on the problems and conflicts in practice that existed after almost four decade of its application and implementation. The Rules has been introduced in 1968 and was applied by most major cargo and shipping owning countries. The research paper will be divided into 4 chapters and at the end of the paper a conclusion on the finding and solution of the problem will be suggested. Each chapter would have their own scope to deal with. Starting with Chapter 1 being the proposal of the paper would include a brief introduction, the problem statement, research methodology that is adopted, limitation of the research, and objective of the studies. Chapter 2 dealt with general terms and main issue surrounding the application of the Rules. Technical terms, type of documents and contract, and also general application of the Rules shall also be explained in details. Chapter 3 would highlight the problems in practice over the years focusing largely base on jurisdiction and uniformity issue. Examples of application from countries that apply the Rules would be analysed. Chapter 4 is the recommendation and conclusion chapter that include highlight on challenges that need to be dealt with, recommendation from international maritime communities on the unification of the rules, suggested solution to overcome the weakness and shortcoming of the rules and also lastly a conclusion from the findings of the research paper.